2019
DOI: 10.1152/ajpheart.00244.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by the mitochondrial unfolded protein response requires ATF5

Abstract: The mitochondrial unfolded protein response (UPRmt) is a cytoprotective signaling pathway triggered by mitochondrial dysfunction. UPRmt activation upregulates chaperones, proteases, antioxidants, and glycolysis at the gene level to restore proteostasis and cell energetics. Activating transcription factor 5 (ATF5) is a proposed mediator of the mammalian UPRmt. Herein, we hypothesized pharmacological UPRmt activation may protect against cardiac ischemia-reperfusion (I/R) injury in an ATF5-dependent manner. Accor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 41 publications
3
98
0
Order By: Relevance
“…Based on all this information, we speculate that a branch of UPR mt induced by ATFS-1 activation is directly involved in the protection from alcohol-mediated muscle dysfunction. Interestingly, although we do not know that UPR mt influences alcohol-induced tissue damage, several studies in mammals indeed showed that UPR mt upregulation is protective from certain stress-induced organ damage (41)(42)(43). Taken together, we propose that mitochondrial dysfunction and consequent UPR mt activation may underlie many pathologies of alcoholic myopathy and further understanding of UPR mt in alcoholic myopathy may lead to a better therapeutic intervention.…”
Section: Discussionmentioning
confidence: 78%
“…Based on all this information, we speculate that a branch of UPR mt induced by ATFS-1 activation is directly involved in the protection from alcohol-mediated muscle dysfunction. Interestingly, although we do not know that UPR mt influences alcohol-induced tissue damage, several studies in mammals indeed showed that UPR mt upregulation is protective from certain stress-induced organ damage (41)(42)(43). Taken together, we propose that mitochondrial dysfunction and consequent UPR mt activation may underlie many pathologies of alcoholic myopathy and further understanding of UPR mt in alcoholic myopathy may lead to a better therapeutic intervention.…”
Section: Discussionmentioning
confidence: 78%
“…Based on this information, we speculate that UPR mt induced by ATFS‐1 activation is directly involved in protection against alcohol‐mediated muscle dysfunction. Interestingly, although we do not know if UPR mt influences alcohol‐induced tissue damage, several studies in mammals have indeed shown that UPR mt upregulation is protective against certain types of stress‐induced organ damage 58‐60 . Studies in both C elegans and mammals showed that UPR mt promotes mitochondrial protein homeostasis, increases mitochondrial protein import, confers innate immunity, and reorganizes metabolic enzymes 11,61‐63 .…”
Section: Discussionmentioning
confidence: 99%
“…In the same study it was also shown that hearts from patients with aortic stenosis, which is often associated with left ventricular overload, exhibited increased expression of genes associated with the UPR mt . In another study, mice in which ATF5 was genetically deleted were used to show that the UPR mt protected the heart against I/R in an ATF5-dependent manner (53). Moreover, in the same study RNAseq results demonstrated the induction of numerous genes in an ATF5-dependent manner during pharmacological induction of the UPR mt .…”
Section: Mitochondrial Proteostasis In Cardiac Pathologymentioning
confidence: 93%
“…Upon accumulation ATF5 is then exported from mitochondria to the nucleus where it acts as a transcription factor that induces genes encoding proteins designed to improve mitochondrial protein folding and rebalance mitochondrial proteostasis (Figure 1F), such as HSPA9, LonP1, and YME1L. ATF5 also serves as a communicator of metabolic stress by temporarily limiting the transcription of OXPHOS genes encoded in nuclear and mitochondrial genomes, while simultaneously increasing nuclear encoded gene transcription of all glycolysis components, and this is thought to maintain cellular ATP levels until mitochondrial dysfunction is resolved (45,53).…”
Section: Mitochondrial Proteostasismentioning
confidence: 99%